Optimization of flooding parameters and enhanced-efficiency development for surface-modified nano-SiO₂ emulsion in low-permeability sandstone reservoirs - Mengke Xin; Dingxue Zhang; Yan Zhang; Jun Chen; Linshuo Yan; Yiwei Qin; Qirui Zhang (PLoS ONE, 2025)
Low-permeability reservoirs, characterized by poor reservoir quality and pronounced heterogeneity, consistently encounter engineering challenges during waterflooding operations, such as suboptimal displacement efficiency and restricted sweep coverage. Nanoemulsions, through wettability alteration and enhancing macroscopic sweep efficiency, are widely applied in the efficient development of low-permeability reservoirs. However, current field applications in Reservoir G exhibit inefficacy, necessitating laboratory experiments to identify factors affecting poor injection performance and enhance oil recovery. This study conducted laboratory core displacement experiments using native cores from the target reservoir, integrated field operational data for injection parameter optimization, and implemented field applications. Results indicate: (1) The modified nano-SiO₂ emulsion, with an average particle size of 26.01 nm, is substantially below the pore-throat dimensions of reservoir cores; (2) Wettability reversal was confirmed through contact angle reduction on oil-wet substrates from 132.9° to 53.6°; (3) Optimal parameters—0.1 mL/min injection rate, 0.3 wt% concentration, and 0.3 PV slug volume—Utilizing dual-slug injection (0.15 PV × 2 + 0.1 PV water spacer) enhanced oil recovery by 18.83%. Segmented injection effectively mitigates particle adsorption-induced plugging and achieves deep reservoir penetration, outperforming single-slug injections. Field experimental results show that segmented injection with water spacers increased daily fluid production from 2.86 m³ to 5.22 m³ and daily oil production from 2.23 t to 4.3 t, retaliating a synergistic mechanism of the modified nano-SiO₂ emulsion in “performance-parameter-mode” optimization.